Uma (auto)etnografia dançante: trajetórias e processos identitários de artistas negros e negras nos cursos de Dança da UFSM - Silveira, Amanda Santos (2020)
Desires and necessities guide this work. The desire to dance also with words and the need to highlight and problematize blackness in the academic space. The text is thought, danced and written through the artistic knowledge of Dance in dialogue with the anthropological, sociological and political studies of the Social Sciences. The main objective of this study is to understand the identity processes of black inviduals in undergraduate Dance courses at UFSM between 2013 and 2018. Therefore, through an methodological (self)ethnographic approach, I build criticism and tensioning about how this process echoes in the life of other black individuals, given that the notion of blackness defines and redefines itself through the length of the formative trajectory as a whole. The structure of this writing is organized in three chapters, through which I peruse since my personal, formative and artistic trajectory, to the discussions about identity, blackness, affirmative actions and education, especially in higher education. In this writing, I describe the construction of the research universe, experiences in the fieldwork and the trajectory of interlocutors who, linked to the theoretical debate, support the research. As a result, I found that the dance formation of identity processes stood out from the Dancer-Researcher-Interpreter Method and the Somatic Approaches of Movement. At the same time, these processes occur beyond graduation, involving family socialization, integration, behavior, and issues related to black collectives. Finally, on the different conceptions of being black and manifesting blackness, the empirical data pointed out that they are not limited as phenotypic issues, but a part of the experiences lived in the trajectory of each of the interlocutors.